The Reception of Pragmatic Linguistics in the Thought of Taha Abderrahmane - mansouri, somia; gouffi, mourad (El Omda in Linguistics and Discourse Analysis, 2024)
This study is concerned with researching the cognitive standard that is the basis for determining the “concept of pragmatics.” By what standard is this concept determined? The highest standard of linguistic structure? Or according to the standard of linguistic usage? Or is it the criterion of the relationship of the linguistic structure to the field of their use together? The thinker and linguistic philosopher, Taha Abd al-Rahman, is considered one of the pioneers of pragmatic linguistic thought, especially in the Arab world, as he was the first to derive the terminological equivalent of “pragmatic linguistics” with “pragmatic linguistics,” which he adopted. Many researchers and scholars later. What are the circumstances of this choice and what are the backgrounds to its reception of pragmatic linguistics?